New hope for tumor immunotherapy: the macrophage-related “do not eat me” signaling pathway - Deng, Han; Wang, Guan; Zhao, Shengyan; Tao, Yiran; Zhang, Zhixiong; Yang, Jinliang; Lei, Yi (Frontiers in Pharmacology, 2023)
The "don't eat me" signaling pathway is extremely active in tumor cells, providing a means for these cells to elude macrophage phagocytosis and escape immune surveillance. Representative markers of this pathway, such as CD47 and CD24, are highly expressed in numerous tumors. The interaction of SIRPα with CD47 reduces the accumulation of non-myosin ⅡA on the cell membrane. The combination of CD24 and Siglec10 ultimately leads to the recruitment of SHP-1 or SHP-2 to reduce signal transduction. Both of them weaken the ability of macrophages to engulf tumor cells. Blocking the mutual recognition between CD47-SIRPα or CD24-Siglec10 using large molecular proteins or small molecular drugs represents a promising avenue for tumor immunotherapy. Doing so can inhibit signal transduction and enhance macrophage clearance rates of cancer cells. In this paper, we summarize the characteristics of the drugs that affect the "don't eat me" signaling pathway via classical large molecular proteins and small molecule drugs, which target the CD47-SIRPα and CD24-Siglec10 signaling pathways, which target the CD47-SIRPα and CD24-Siglec10 signaling pathways. We expect it will offer insight into the development of new drugs centered on blocking the “don’t eat me” signaling pathway.